The trowel and the sickle. Italian archaeology and its Marxist legacy - Cella, Elisa; Gori, Maja; Pintucci, Alessandro (Ex Novo: Journal of Archaeology, 2016)
During the second post-war period (1945-1960s), the Italian Communist party was a hub of intellectuals, and as such influenced the development of Italian archaeology as well. Marxist ideology indeed was perceived as means to enfranchise the discipline from the old academia. Focusing on of the so-called “Roman school” of archaeology, this paper analyzes the influence of communist and Marxist ideologies on the discipline’s development. In particular we will present two prominent and charismatic archaeologists Renato Peroni and Andrea Carandini. It is argued that while the Marxist research trajectories were characterized by an initial innovative and driving force that revolutionized Italian archaeology, the collapse of the Italian Communist Party and the resulting downfall of its intellectual tradition determined the exhaustion of the discipline’s innovative potential.